Role of the PAR4 Thrombin Receptor in Stabilizing Platelet-platelet Aggregates as Revealed by a Patient with Hermansky-Pudlak Syndrome - Covic, Lidija; Singh, Christopher; Smith, Hedy; Kuliopulos, Athan (Thrombosis and Haemostasis, 2002)
Individuals with Hermansky-Pudlak Syndrome (HPS) lack platelet dense granules and have no ADP-autocrine response. Despite these platelet deficiencies, HPS patients exhibit a surprisingly mild bleeding phenotype. We hypothesize that activation of the PAR4 thrombin receptor compensates for the lack of an ADP-autocrine response by the P2Y12 ADP receptor in individuals with HPS. Here, we determine that PAR4 activation by thrombin occurs well after ADP release from dense granules in normal individuals. However, the signal from PAR4 stabilizes platelet-platelet aggregate formation in the absence of P2Y12 activation by ADP. Thus, the strong signal emanating from PAR4 during platelet aggregation would provide an explanation for the mild bleeding diathesis of HPS.
Keywords: Hermansky-Pudlak Syndrome (HPS); PAR4; PAR1; P2Y12